Physical activity, sleep and weight management in the COVID-19 era: a case report - Adamakis, M. (Journal of Physical Education and Sport, 2021)
The evolving COVID-19 pandemic has caused community-wide lockdowns, resulting in social isolation. Currently the routine physical activities (PA) of millions of people worldwide has been disrupted, while there is strong recommendation for individuals to remain physically active by taking short active breaks. The case study reported aims at providing detailed information of a male individual who was physically active before the community-wide lockdown and attempted to remain physically active during the COVID-19 pandemic. It presents data, over eight weeks in total (4 x 2-week periods), of daily PA (steps and outdoor workout sessions), sleep monitoring (total and deep sleep time), and body weight and composition, as well as a structured exercise programme developed and implemented during the quarantine period. PA and sleep data were objectively measured with the use of a wearable PA monitor (i.e. Garmin Vivofit 4). The daily 30-min training programme included High Intensity Circuit Training (HICT) with the use of the 7 Minute Workout® app for Android, as well as body weight training (e.g. push-ups, squats). Results showed that PA based on step count has plummeted during self-isolation measures, however a home-based, individualized, app-driven HICT and body weight training programme, under the continuous monitoring of an exercise expert, has the potential to outweigh the detrimental effects of lack of movement. In order to increase daily PA up to the level before the lockdown, active commuting is an indispensable factor. Lastly, insufficient sleep quality and duration may undermine weight maintenance success and exercise performance. Implications related to these themes are further discussed.